2002
DOI: 10.1108/09566160210424608
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of groundwater vulnerability and water policy reform in India

Abstract: Water is a basic human need, a finite life support system and a key to prosperity. Unplanned industrialisation, urbanisation and impact of liberalised import of wastes intended for recycling have negatively affected the water environments in India. This is further exaggerated by lack of discipline and a weak obligation towards conservation and pollution prevention. Measures have to be especially taken to resolve the groundwater problems. While groundwater resources are quite well assessed, overexploitation sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Many of the rivers, lakes and coastal environments have been polluted by industrial effluents. Too diminutive attention has been paid to control the disposal of hazardous industrial wastes to prevent risk to people or outflow to the environment (Chaudhary et al , 2002). In various manufacturing industries, toxic materials are extensively used for product development and process operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of the rivers, lakes and coastal environments have been polluted by industrial effluents. Too diminutive attention has been paid to control the disposal of hazardous industrial wastes to prevent risk to people or outflow to the environment (Chaudhary et al , 2002). In various manufacturing industries, toxic materials are extensively used for product development and process operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bacteria. Indian cities are estimated to generate 20 million m 3 of sewage per day, and only 10% of this sewage is treated prior to reaching groundwater or surface water resources (8). Furthermore, the majority of Indian domestic waste is improperly disposed.…”
Section: Present Groundwater Quality In Indiamentioning
confidence: 99%
“…Pesticide consumption increased rapidly in India through the green revolution and into the mid 1990s, reaching 74.323 billion metric tons in the year 1995 (8). Pesticide residues affect groundwater for longer time periods than surface water as the soil can accumulate these contaminants, which may steadily leach into groundwater.…”
Section: Present Groundwater Quality In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Kole & Bagchi (1995) conducted a survey by drawing drinking water samples from various hand pumps and wells around Bhopal and found that more than half of the samples were contaminated with Organo Chlorine pesticides above the EPA standards. Chaudhary et al (2002) showed the elevated levels of pesticides in the groundwater aquifer in Howrah district rendering the water unfit for drinking purposes. Sankararamakrishnan et al (2005) conducted the groundwater quality analysis of Kanpur, India and reported the presence of high concentration of organochlorine and organophosphorus pesticides.…”
Section: Introductionmentioning
confidence: 99%